Developing novel life skills and experiences: a pilot study with Functional Advanced Didactics - Santolo Ciccarelli; Chiara Scuotto; Luigi Aruta; Francesco V Ferraro; Maria Luisa Iavarone (Firenze University Press, 2023)
The pandemic has produced profound changes in teaching activities, with consequences on the educational processes and social development of students. In this sense, the following contribution explores the potential of Advanced Functional Didactics (DAF), a didactic proposal that aims to deliver traditional didactic contents through motor activity. Carried out in a difficult social context, namely the IC Ristori of Naples, located in the Forcella district, the study involves a second class of primary school and a first class of lower secondary school. The experimental hypothesis of this research is that the introduction of the DAF can bring benefits to the physical, psychological, social and learning abilities of the learners. This pilot study was the first to carry it out, thus proposing to verify the impact of this methodology on students to collect useful responses to improve it.   Lo sviluppo di nuove abilità ed esperienze: uno studio pilota con la Didattica Avanzata Funzionale. La pandemia ha prodotto profondi cambiamenti nelle attività didattiche, con conseguenze sui processi formativi e di sviluppo sociale degli studenti. In tal senso, il seguente contributo esplora le potenzialità della Didattica Avanzata Funzionale (DAF), una proposta didattica che mira ad erogare i contenuti didattici tradizionali attraverso l'attività motoria. Realizzato in un contesto sociale difficile, ossia l'IC Ristori di Napoli, sito nel quartiere di Forcella, lo studio coinvolge una classe seconda della scuola primaria e una classe prima della scuola secondaria di primo grado. L'ipotesi sperimentale di questa ricerca è che l'introduzione della DAF possa apportare benefici alle capacità fisiche, psicologiche, sociali e di apprendimento dei discenti. Questo studio pilota è stato il primo a realizzarla, proponendosi quindi di verificare l'impatto di questa metodologia sugli studenti allo scopo di raccogliere risposte utili a migliorare quest'ultima.